Assessing the Impacts of Organizational Culture and Sales Promotion on Consumer Buying Behavior: A Case of Telecom Sector - Rehman, Fazal ur; Md Yusoff, Rosman; Ismail, Fadillah (Journal of Social Transformation and Regional Development, 2019)
This study aims to examine the impacts of organizational culture and sales promotion on the buying behavior of Pakistani consumer’s. This study has collected data through self-administered questionnaires from the consumers of Telenor, a telecommunication company in Pakistan. The collected data were analyzed through linear regressions to determine results. This study is based on the marketing event of Telenor. Results have indicated that organizational culture and sale promotions have positive significant relationship with the buying behavior of Pakistani consumers in telecom sector. It has noted that organizational culture is positively correlated to sales promotion. The study has suggested that marketing professional can apply the technique of organizational culture in sales promotion to affect the buying behavior of Pakistani consumers